Pliocene to Pleistocene vertical movements in the forearc of the Lesser Antilles subduction: insights from chronostratigraphy of shallow-water carbonate platforms (Guadeloupe archipelago) - Mϋnch, P.; Cornee, J.; Lebrun, J.; Quillevere, F.; Verati, C.; Dobrinescu, M.; Demory, F.; Smith, B.; Jourdan, Fred; Lardeaux., J.; Min, L.; Leticee, J.; et al. (Geological Society Publishing House, 2014)
An integrated stratigraphic study was conducted on the shallow water carbonate platforms of theGuadeloupe archipelago to refine the tectonic evolution of the Lesser Antilles forearc. The carbonate platforms are now dated to the Zanclean–Calabrian interval, and their demise occurred between 1.5 and 1.07 Ma. The precise chronostratigraphy allows dating of the main extensional tectonic events since the late Miocene. An initial episode occurred during the late Miocene, related to the reactivation of inherited N130°E-trending shear zones, and led to the emergence of most parts of the forearc. Subsequently, Zanclean to early Piacenzian carbonate platforms developed in association with a general subsidence of the forearc. During the late Piacenzan, a second extensional episode occurred. At this time La Désirade underwent major uplift and emergence whereas most of the forearc remained submerged. Prior to 1.07 Ma, a third north–south extensional episode occurred and led to the final demise of the carbonate platforms. Thus the forearc was characterized by general subsidence since the early Pliocene interrupted by three main extensional episodes and related differential uplifts. This suggests that the Lesser Antilles subduction is probably erosive north of latitude 15°N since c.5 Ma, related to aseismic ridge subduction